Mascarado em trânsito. A máscara Mapiko de Moçambique - Rhormens, Mariana (2023)
This article presents the Mapiko masks of Mozambique, discusses their origins, aesthetics, dances, musicalities, rhythms, confections, traditions and transformations. It brings to the debate the concept of liminality from the thoughts of Victor Turner and Van Gennep. It discusses the liminality of the masquerade in the Mapiko demonstration of Mozambique and discusses the liminoid character of the mask and the possibilities of inhabiting the “between-places” by masquerading.